2012
DOI: 10.1152/ajpheart.00984.2011
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic glutamate receptors in the external lateral parabrachial nucleus participate in processing cardiac sympathoexcitatory reflexes

Abstract: Stimulation of cardiac sympathetic afferents during myocardial ischemia with metabolites such as bradykinin (BK) evokes sympathoexcitatory reflex responses and activates neurons in the external lateral parabrachial nucleus (elPBN). The present study tested the hypothesis that this region in the pons processes sympathoexcitatory cardiac reflexes through an ionotropic glutamate receptor mechanism. The ischemic metabolite BK (0.1-1 μg) was injected into the pericardial space of anesthetized and bilaterally vagoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 64 publications
(130 reference statements)
3
13
0
Order By: Relevance
“…Some LPBN neurons have been reported to mediate respiratory changes accompanying changes in BP (23,35). We have observed that cardiac sympathetic afferent stimulation activates neurons in the elPBN (16,17) and evokes pressor reflexes that are reduced after inhibition of the elPBN (11), suggesting that the cardiovascular neurons responsive to cardiac afferent input likely also exist in the elPBN. Thus the present study was designed to determine if cardiovascular neurons are present in the elPBN and to examine their contribution to central processing of cardiac sympathetic afferent input.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Some LPBN neurons have been reported to mediate respiratory changes accompanying changes in BP (23,35). We have observed that cardiac sympathetic afferent stimulation activates neurons in the elPBN (16,17) and evokes pressor reflexes that are reduced after inhibition of the elPBN (11), suggesting that the cardiovascular neurons responsive to cardiac afferent input likely also exist in the elPBN. Thus the present study was designed to determine if cardiovascular neurons are present in the elPBN and to examine their contribution to central processing of cardiac sympathetic afferent input.…”
mentioning
confidence: 83%
“…ACTIVATION OF CARDIAC SYMPATHETIC afferent nerves, especially during myocardial ischemia, causes cardiac pain and excitatory reflex cardiovascular responses characterized by increases in sympathetic outflow, elevations in blood pressure (BP) and heart rate (HR), and tachyarrhythmia (11,12,24,34). These reflex responses increase the morbidity and mortality of patients with heart diseases, because they exacerbate the extent of ischemia and infarction, which leads to severe heart failure and lethal ventricular arrhythmias (11,24,34).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To eliminate the influence of vagal cardiac afferents that could mask the CSR responses to stimulation of sympathetic afferents and minimize the BP “buffering” action of arterial baroreceptors, bilateral cervical vagotomy and sinoaortic denervation with sectioning of carotid sinus nerves were conducted in rats used in first four protocols (see in following protocols), as described previously 3,76 . Vagotomy was not performed in rats used in the last protocol (described in protocols section) for examining the CSR responses in vagus-intact animals.…”
Section: Methodsmentioning
confidence: 99%